Teaching English in the industry 4.0 and disruption era: Early lessons from the implementation of SMELT I 4.0 DE in a senior high lab school class - Suherdi, Didi (Universitas Pendidikan Indonesia, 2019)
Industrial revolutions always bring with them radical changes and, with various degrees, disruptive effects on the existing or ongoing technologies. In this conjunction, radical changes in doing education are now forthcoming, and some traditional ones are being disrupted. Many proposals are now being introduced to respond to the demands of the era. In relation to the teaching of English, the writer proposed a model, called SMELT I 4.0 DE, standing for a Synergetic Multilayered English Language Teaching for Industry 4.0 and Disruption Era. While the effects of each layer of the model (ICTC, SRLI, and TVCD) on students’ ELT learning have been extensively reported, those of the layers in a synergetic whole are not yet well-investigated. Hence, a study on the use of SMELT I 4.0 DE is theoretically motivating and practically enlightening. For the very reason, a one-semester pilot project implementing the model in an English as a foreign language (EFL) class in Universitas Pendidikan Indonesia Senior High Lab School has been conducted in the first semester of 2018/2019. This paper is intended to present findings from the aforementioned SMELT I 4.0 DE pilot project. The data were collected through questionnaires, interviews, document analysis, and observations from a class of 29 students. It is shown that ICTC has been successful in (1) increasing students motivation and engagement, (2) giving them positive experience in utilizing students digital devices for educational purposes, and (3) encouraging students creativity; SRLI has triggered students self-regulation in planning, doing, and assessing their learning, self-selection of learning focus and materials, and strategies; and TVCD has enhanced students learning through self-discipline, honesty, confidence, collaboration, communication, and hardworking. In conclusion, the implementation of SMELT I 4.0 DE has resulted in significant progress in all aspects of students’ learning under study.